2020
DOI: 10.1088/1755-1315/558/3/032003
|View full text |Cite
|
Sign up to set email alerts
|

Study of influences of rock hardness on crack evolution rule under hydraulic fracturing

Abstract: In order to study the crack evolution rules of hydraulic fracturing rock with different hardness, a numerical model of hydraulic fracturing rock was established. It explored the expansion length, expansion width, propagation rate of crack and initiation pressure of hydraulic fracturing different hardness rocks. The results show that the expansion length, the propagation rate along length and the initiation pressure of crack were positively correlated with the rock hardness, and the expansion width and propagat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…For example, effective rock fracture may improve the ore recovery ratio through effective separation of minerals along their grain boundaries in mineral processing 32 35 . Jialiang Liu et al studied the crack evolution rules of hydraulic fracturing rock with different hardness 36 . By conducting a series of calculation analyses of the crack rheological fracture under different hydraulic pressures, Yanlin Zhao et al found that wing crack propagation can be divided into two parts: the transient crack propagation at very high velocity and subcritical crack propagation at extreme low velocity 37 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, effective rock fracture may improve the ore recovery ratio through effective separation of minerals along their grain boundaries in mineral processing 32 35 . Jialiang Liu et al studied the crack evolution rules of hydraulic fracturing rock with different hardness 36 . By conducting a series of calculation analyses of the crack rheological fracture under different hydraulic pressures, Yanlin Zhao et al found that wing crack propagation can be divided into two parts: the transient crack propagation at very high velocity and subcritical crack propagation at extreme low velocity 37 .…”
Section: Introductionmentioning
confidence: 99%
“…The distribution and expansion of its fissures directly affect mining safety, such as underground water inrush and roof failure which are all developed and evolved from cracks and other weak surfaces [8,9]. In underground mining, the development of fissures is one of the major causes leading to the destruction of rock projects [10][11][12]. Understanding the crack propagation mechanism can provide a feasible basis for engineering safety design.…”
Section: Introductionmentioning
confidence: 99%